Perforated ileus after L5-S1 anterior lumbar interbody fusion: a case report presentation - Mahoney, J. Ryan; Barnes, David; Pahl, Douglas (AME Case Reports, 2019)
Acute colonic pseudo-obstruction (ACPO) as a result of anterior lumbar spinal surgery can result in colonic perforation. ACPO is often treated successfully with conservative measures, reserving surgical intervention for severe cases. The most severe cases can result in colonic perforation with a concomitant high mortality rate. Herein we outline a case of a 72-year-old male with multiple medical comorbidities and history of intermittent constipation who underwent anterior lumbar interbody fusion (ALIF) of L5-S1. The patient’s multiple medical comorbidities placed him at risk for ACPO. His postoperative course was complicated by an ileus. The patient initially underwent conservative management that failed, resulting in colonic perforation. He underwent urgent exploratory laparotomy and repair of colonic perforation by the general surgery service. The patient had spontaneous return of bowel function on postoperative day 5, and at 6 months, he was doing well. The main purpose of this case report is to present a unique case of colonic perforation after ALIF. Understanding patient risk factors can help in early identification and treatment of potentially life-threatening complications. Surgeons should discuss the possibility of this complication with the patient during surgical counseling for anterior lumbar surgery.